Responding to global infectious disease outbreaks: Lessons from SARS on the role of risk perception, communication and management - Smith, Richard D. (Soc Sci Med, 2006)
With increased globalisation comes the likelihood that infectious disease appearing in one country will spread rapidly to another, severe acute respiratory syndrome (SARS) being a recent example. However, although SARS infected some 10,000 individuals, killing around 1000, it did not lead to the devastating health impact that many feared, but a rather disproportionate economic impact. The disproportionate scale and nature of this impact has caused concern that outbreaks of more serious disease could cause catastrophic impacts on the global economy. Understanding factors that led to the impact of SARS might help to deal with the possible impact and management of such other infectious disease outbreaks. In this respect, the role of risk—its perception, communication and management—is critical. This paper looks at the role that risk, and especially the perception of risk, its communication and management, played in driving the economic impact of SARS. It considers the public and public health response to SARS, the role of the media and official organisations, and proposes policy and research priorities for establishing a system to better deal with the next global infectious disease outbreak. It is concluded that the potential for the rapid spread of infectious disease is not necessarily a greater threat than it has always been, but the effect that an outbreak can have on the economy is, which requires further research and policy development.